MSME Digitalization: Strengthening Fintech Adoption Through Tri-Literacy to Enhance Sustainable Entrepreneurship - Febrianawati, Febrianawati; Hidayat, Nur; Yuana; Areskeia, Indera; Hura, Meiherni (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are crucial to the Indonesian economy, although they encounter obstacles in leveraging digital technologies. Inadequate literacy levels, encompassing digital, financial, and entrepreneurial literacy, impede the effective adoption of financial technology (fintech), which could serve as a strategic remedy to enhance organizational performance. This study examines the impact of Tri-Literacy on fintech adoption and its consequences for MSME performance. The research employs a quantitative approach using a survey of 300 MSMEs in Pontianak City and its vicinity. The research instrument is a questionnaire with a 1–5 Likert scale, developed based on indicators of Tri-Literacy, Fintech Adoption, and MSME Performance. Data were analyzed using Structural Equation Modeling (SEM) with WarpPLS 8.0 to assess validity, reliability, coefficients of determination, and path coefficients. The findings indicate that all Tri-Literacy variables significantly and positively influence fintech adoption, which in turn significantly and positively affects MSME performance. Entrepreneurial literacy provides the largest contribution to both fintech uptake and MSME performance. The research model demonstrates validity and relevance, yielding an R² value of 0.762 for Fintech Adoption and 0.844 for MSME Performance. The performance construct used in this study captures not only short-term financial outcomes, but also aspects of resilience, adaptability, and long‑term viability, thereby reflecting the broader concept of sustainable entrepreneurship.